Empowering Municipal Sustainability. A Guide for Towns, Cities, and Citizens. - Lajoux, Alexandra Reed (De Gruyter, 2022)
Amidst growing awareness over the past half century that human activity threatens our natural environment, many of the world’s largest cities have played a role in the sustainability movement, as seen by such initiatives as Day of Cities sponsored by the United Nations. And now local governments in towns and smaller cities are beginning to play a more prominent role in the green movement. This book, inspired by the author’s own experience as a citizen activist and local candidate, is a guide for local governments and citizens wishing to launch sustainability campaigns and programs that make a lasting difference in our world. Alexandra Reed Lajoux addresses the popular „green city“ topic but focuses on smaller municipalities, which are more numerous than big cities, and in greater need of guidance. With a visionary foreword by Ben G. Price, National Organizer, Community Environmental Legal Defense Fund and author of How Wealth Rules the World, the book discusses the most critical environmental, economic, and engineering realities of municipal life and leadership in our times, ranging from rights of nature, to rollback tax rates, to green infrastructure, to gentrification. It will appeal to a broad range of town or city government employees and elected officials, as well as local activists, contemplating the issues of managing and funding sustainability that all localities worldwide face at some level.
Keywords: Nachhaltige Stadtentwicklung; Stadtpolitik; Stadtentwicklungspolitik; Stadtgrün; Stadtökologie; Ökologische Stadterneuerung; Infrastrukturverbesserung; Umweltverträglichkeit; Sozialverträglichkeit; Grüne Infrastruktur